(untitled) (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2018)
Inventory study on aquatic plants was conducted in Rawa Taliwang lake, located at West Nusa Tenggara. The area of this water body total ranges from 584 to 913 ha and most of the water surface area is convered with aquatic macrophytes. In 1990 the fish yield was 241 ton and than declined to 36,9 ton in 1994. The objective of this study was to evaluate the species distribution and abundance of the aquatic plants in the lake. Field investigations for ecological study of aquatic plants were conducted in June and in October 1999, representing dry and rainy seasons, repectively. Result of this study showed that the importance values of the aquatic plant during the wet seasons (6,70-71,06%) were not significant different compared than that in dry seasons (6,59-70,13%). The aquatic plants found in Rawa Taliwang were consisted of 16 species and they covered 70-80% of the water surface area. The important floating aquatic plants were Salvinia molesta, Nelumbo lutea, Nymphaea pubescens, Pistia stratiotes and Monochoria vaginalis, whereas the submerged aquatic plants were dominated by Hydrilla verticillata, Ceratophyllum demersum, and Najas indica. Keywords : aquatic plants, density, dominancy, frequency, importance value